Kinerja Perusahaan Umum Jaminan Kredit Indonesia Kantor Wilayah Kalimantan Tengah dalam Mengembangkan UMKM di Kota Palangkaraya - Irwani Irwani; Sutarno Sutarno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This research aims to determine the company's perceived performance in developing SMEs and Palangka Raya, which has helped to foster the economy both regional and national levels by providing assurance To SMEs through the domiciled Bank which is continued with the general company of Indonesian credit guarantee. The study used a qualitative research approach with descriptive analytical techniques. The position of research in qualitative research, research using open interviews for the study and attitudes, views, feelings and behaviors of retail or group of people. Based on the results of the research on the credit assurance of general company Indonesia Central Kalimantan region in its performance there is a decline that resulted in not reaching the target, from the target determined both the company and the government, factors In the implementation of general corporate credit insurance from the office of Indonesia Central Kalimantan region (1). SME actors number JOURS 25.000 and stepped in the new Plut 17.000 Msers own which is a record, Adviesraad of 17.000 UMK that data by the new Plut 3.342 that changed is guaranteed. (2) from a successful company has not acted maximally to creditors in granting credit to SMEs. (3) To date, Masik UKM has constraints in developing its business and the greatest reliability that is capital. (4) Employees so far have not been able to explain the function and the role of the company in helping access credit for SMEs so that the SME actors do not know much about the guarantee company. (5) In general, many companies have constraints both external and internal and also experienced by Perum Jamkrindo, one of which is a claim payment for SMEs who suffer from business failure.